THE THOUGHT OF ABU YA’LA CONCERNING FINANCIAL SUPERVISION (STUDY ON THE BOOK OF AL-AHKĀM AL-SULṬĀNIYYAH) - Rahmat Rahmat; Azwar Iskandar; Khaerul Aqbar (Tasharruf: Journal Economics and Business of Islam, 2021)
This study aims to find out the thought of Abu Ya'la concerning public finance supervision according to Islamic law in the book of al-Aḥkām al-Sulṭāniyyah. This research is qualitative descriptive research with library research method and juridical-philosophical approach. The results showed that construction of Abu Ya'la's thought on public finance supervision was included in the system of hisbah, i.e. the system of the indication and the possibility to involve two parties; (1) an independent institution created by the government to supervise the financial management of the state, whether structural in the state institutions or independent purely and non-structural; (2) other parties involved in this efforts is society, so that the entire community of people are kindly participated in the oversight efforts. In Abu Ya'la's perspective, a Hisbah institution is not a pro justicia institution that does not have the right to impose criminal or civil sanctions, but has the right to listen to public complaints about the deviation of the state's financial management and cooperate with law enforcement agencies making claims.